ORGANIC PRODUCTION IN FUNCTION OF ENVIRONMENT PROTECTION IN SERBIA – CONDITION AND REGULATIONS - Katić, Branko; Cvijanović, Drago; Cicea, Claudiu (Economics of Agriculture, 2008)
Organic agriculture is based on application of assigned methods of organic production. It gains more significance, because it brings a man closer to nature, from which he parted, it represents almost full harmony with environment preservation demands, and finally, it enables the population to feed on the products based on the natural processes, using organic and mineral materials. Products based on organic production are increasingly sought, especially in highly developed states. Their placement is certain, because the demand highly surpasses the supply. For that reason they get better prices than the conventional production goods. Republic of Serbia has very good conditions for founding this kind of production. The environment is preserved, especially in mountainous areas, which take 71,5% of Central part of the Republic (51,7% of whole Republic). Artificial fertilizers are much less used in these areas, as is agro-mechanization, which pollutes the environment. Most of these areas have high quality water, clean air and are far from the roads and other sources of environment pollution. Organic production is processing by very high criteria, regulated by special decrees. Same goes for the environment preservation decrees. These decrees exist in Serbia as well, and are well coordinated with European Union legislation. This paperwork reviews the state of environment, organic production and regulatory rules in these two parts of Republic of Serbia.